Presenting XML-based Medical Discharge Letters According to CDA - Bludau, H. B.; Wolff, A.; Hochlehnert, A. J. (Methods of Information in Medicine, 2003)
The HL7 Clinical Document Architecture (CDA) is an important XML-based standard for the representation of clinical documents.Objectives: The use of Markup Languages could satisfy the demands of involved healthcare staff as well as the needs of patients, to receive an overview of the patient’s treatment during the hospital stay. The standardization efforts of different groups dealing with this problem have demonstrated progress, but have not, as yet, achieved a routinely usable result. In particular, differentiating information according to a hierarchical order has not been published to date.Methods: A retrospective analysis of 60 discharge letters from a cardiology ward (ward A) as well as 60 discharge letters from a gastroenterology ward (ward B) were extracted from the central hospital information system, by taking every fifth discharge letter issued over a one year period.Results: An XML-based prototype for medical discharge letters has been put in place representing the required information units and information elements. By means of an XSL-stylesheet, a detailed representation of the conventional discharge letter has been produced that is platform independent and permits the recurrent use of information units.Conclusions: Through the introduction of definitions like information elements and information units, progress in the development of CDA level two and three might be realized. We present a method by which discharge letters can be used by an Internal Medicine Department. This concept is implemented in a XML-based prototype allowing a special view on XML data to generate this document type.
Keywords: HL7; CDA; XML; discharge letter